Virulence Pattern and Genomic Diversity of Vibrio cholerae O1 and O139 Strains Isolated From Clinical and Environmental Sources in India - Kanampalliwar, Amol; Singh, Durg Vijai (Frontiers in Microbiology, 2020)
Vibrio cholerae is an autochthonous inhabitant of aquatic environment. Several molecular methods were used for typing V. cholerae strains, but there is no proper database for such scheme including multilocus sequence typing for V. cholerae O1 and O139 strains. We used 54 V. cholerae O1 and three O139 strains isolated from clinical and environmental sources and regions of India, during the time period of 1975 - 2015 to determine the presence of virulence genes and production of biofilm. We devised a MLST scheme and developed database for typing V. cholerae strains. Also, we performed pulsed-field gel electrophoresis to see the genomic diversity among them and compared with MLST. We used MEGA 7.0 software for alignment and comparison of different nucleotide sequences. The advanced cluster analysis was performed to define complexes. All strains of V. cholerae, except five strains, showed variation in phenotypic characteristics but carried virulence associated genes indicating they belonged to El Tor/ hybrid/ O139 variants. MLST analysis showed 455 sequences types among V. cholerae strains irrespective of sources and places of isolation. With these findings, we set up an MLST database on PubMLST.org using BIGSdb software for V. cholerae O1 and O139 strains and is available at https://pubmlst.org/vcholerae/ under O1/ O139 scheme. PFGE fingerprint showed six fingerprint patterns namely E, F, G, H, I and J clusters among 33 strains including strain N16961 carrying El Tor ctxB of which cluster J representing O139 strain was entirely different from other El Tor strains. Twenty strains carrying Haitian ctxB showed fingerprint pattern classified as cluster A. Of the five strains, four carrying classical ctxB comprising two each of El Tor and O139 strains and one El Tor strain carrying Haitian ctxB clustered together under cluster B along with V. cholerae 569B showing pattern D. This study thus indicates that V. cholerae strains are undergoing continuous genetic changes leading to emergence of new strains. MLST scheme was found more appropriate compared to PFGE that can be used to determine the genomic diversity and population structure of V. cholerae.